A National Survey of Assessment Instruments Taught by Counselor Educators. (4th September 2013) - Neukrug, Edward; Peterson, Christina Hamme; Bonner, Matthew; Lomas, Gabriel I.
Abstract : This study reports results of a questionnaire of 210 counselor educators regarding assessment instruments covered in their assessment courses. Instruments are ranked on how extensively they are covered, and comparisons of coverage are made by assessment category (e.g., educational, clinical) and by instructor and program characteristic (e.g., Council for Accreditation of Counseling and Related Educational Programs [CACREP] vs. non‐CACREP). Suggestions regarding which assessment techniques to cover in a basic counselor education testing and assessment course are made.